Electronic structure and magnetic assets of FeCoGaO4 nanoparticles: An XANES investigation - Sharma, Aditya; Varshney, Mayora; Kumar, Yogesh; Lee, Byeong-hyeon; Won, Sung Ok; Chae, Keun Hwa; Vij, Ankush; Sharma, Ram K.; Shin, Hyun-Joon (Pergamon Press Ltd., 2022)
In this study, FeCoGaO4 nanoparticles, which have rarely been reported, have been synthesized using a sonication-assisted hydrothermal method. X-ray diffraction (XRD) and transmission electron microscopy (TEM) results have revealed the formation of a single-phase compound with a particle size of 10-20 nm. X-ray absorption near-edge structure (XANES) investigations confirmed the presence of Fe3+, Ga3+ and Co2+ ions in FeCoGaO4. High saturation magnetization (Ms) (-50 emu/g), remanent magnetization (Mr) (10 emu/g) and coercivity (-630 Oe) are observed at 50 K. A lower coercivity (28 Oe), and Mr (0.11 emu/g) are observed at 300 K. The origin of magnetism in the FeCoGaO4 nanoparticles has been mechanistically discussed considering the plausible magnetic interactions among the constituent ions in the material.